Penerapan Sistem ERP Dalam Perencanaan Produksi Dan Pengendalian Persediaan Di PT Konimex - Novita Dyah Pratiwi; Huda Atma Dirgantara, Chairul (Jurnal Bisnis Administrasi dan Manajemen, 2025)
This research explores the implementation of the Enterprise Resource Planning (ERP) system in production planning and inventory control at PT Konimex, a pharmaceutical manufacturing company in Central Java, Indonesia. The study uses a qualitative descriptive method with data collected through direct observation, interviews with PPIC (Production Planning and Inventory Control) staff, and system documentation. Observations were conducted over six weeks, allowing the researcher to understand how the ERP system supports forecasting, raw material management, and scheduling. Interviews revealed ERP’s role in managing production flow, stock control, and daily operational decisions. The ERP system also facilitates monitoring using indicators such as Service Level and Days of Inventory (DOI), helping ensure product availability and timely delivery. Data analysis followed Miles and Huberman's approach: data collection, reduction, display, and conclusion drawing. The study concludes that while ERP significantly enhances efficiency and coordination in PPIC functions, challenges remain, including demand fluctuations and limited production capacity. Recommendations include developing a more adaptive production strategy and enhancing ERP reporting features for more integrated and real-time inventory data. These improvements can support faster decision-making and help the company maintain high customer satisfaction through better production and stock control.